2020
DOI: 10.3389/fpsyg.2020.00794
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Autistic Traits on Social Orienting in Typically Developing Individuals

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder characterized by wide ranging and heterogeneous changes in social and cognitive abilities, including deficits in orienting attention during early processing of stimuli. Investigators have found that there is a continuum of autism-like traits in the general population, suggesting that these autistic traits may be examined in the absence of clinically diagnosed autism. To provide evidence for the continuum of autistic traits in terms of soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
(49 reference statements)
0
4
1
Order By: Relevance
“…This contrasts with a previous study that reported a negative correlation between AQ scores and gaze-cueing effect, but no correlations between AQ scores and arrow-cueing effect [19] , suggesting a reduced salience of social gaze in individuals with high autistic traits. The present results also contrast with another recent study that reported that, in a gaze-cueing paradigm, the cueing effect was larger for individuals with low AQ than for individuals with high AQ [21] . The discrepancies between the present and previous results might be ascribed to the small number of subjects in the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This contrasts with a previous study that reported a negative correlation between AQ scores and gaze-cueing effect, but no correlations between AQ scores and arrow-cueing effect [19] , suggesting a reduced salience of social gaze in individuals with high autistic traits. The present results also contrast with another recent study that reported that, in a gaze-cueing paradigm, the cueing effect was larger for individuals with low AQ than for individuals with high AQ [21] . The discrepancies between the present and previous results might be ascribed to the small number of subjects in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Higher scores in the AQ test were also associated with impaired interpretation of nonverbal aspects of social communication, such as hand gestures and facial expressions [15] , impaired facial recognition [16] and impaired social learning [17] , [18] . In addition, a few studies also reported differences in gaze-triggered orienting in TD subjects with low and high levels of autistic traits [18] [21] . However, it is still not fully understood how gaze orienting in individuals with different levels of autistic traits is differentially modulated by facial expressions and direct eye contact.…”
Section: Introductionmentioning
confidence: 99%
“…The autism-spectrum quotient (AQ; Baron-Cohen et al, 2001) is a questionnaire used as a screening tool for autism in psychiatric and psychological diagnostics (Huang et al, 2020;Woodbury-Smith et al, 2005). It is also applied in research to measure autistic traits in the general population (e.g., Lewton et al, 2019;Lin et al, 2020;Yaxu et al, 2020). In particular, its ten-item short form (AQ-10; Allison et al, 2012) can be an efficient measure for research purposes (e.g., Bertrams & Schlegel, 2020;Gollwitzer et al, 2019;Lundin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that TD individuals who are high in autistic traits perform similarly to individuals with ASD on various tasks. For example, TD individuals who are high in autistic traits exhibit worse performance in gaze‐triggered orienting tasks than individuals who are low in autistic traits (Hudson et al, 2012; Lassalle & Itier, 2015; Lin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%